Failure of a Pure Progestogen Contraceptive to Affect Serum Levels of Iron, Transferrin, Protein-bound Iodine, and Transaminase. Issue 5716 (25th July 1970) - Powell, L. W.; Jacobi, J. M.; Gaffney, T. J.; Adam, R.
Abstract : Medroxyprogesterone acetate, a pure progestational agent which is not metabolized to oestrogen, was given to 30 women and shown to have no effect on the serum levels of iron, total iron-binding capacity, transferrin, and protein-bound iodine. Eighteen of these women had previously taken oral contraceptives of the combined oestrogen-progestogen "sequential" type, and during that time these serum levels were raised. Nevertheless, the levels all fell significantly after medroxyprogesterone acetate was given and the "sequential" oral contraceptive was stopped. In a further 12 postpartum women the serum levels did not change significantly after medroxyprogesterone acetate. These observations strongly suggest that raised plasma protein levels resulting from the administration of oral contraceptives are due to the oestrogen component.